Manufacturing and Characterization of Composite Boards from Corn Husk Fiber, Water Hyacinth Fibers, and Sawdust Using Epoxy Resin - Frida, Erna; Pratyka, Venna (Journal of Technomaterial Physics, 2024)
Composite board has been made with corn husk fiber (CHF), water hyacinth fiber, and wood sawdust using epoxy resin as an adhesive. The composition of each fiberwas varied, and physical tests (density, porosity, water absorption, and thickness expansion) and mechanical tests (modulus of elasticity (MOE), modulus of rupture (MOR), and compressive strength) were carried out, and microstructure was analyzed using SEM-EDX. The results of testing the physical and mechanicalproperties with optimum results were density of 1.03 g/cm3, porosity of 10.48%, water absorption capacity of 10.22%, thickness expansion of 2.91%, MOR 256.05kgf/cm2, MOE 228 kgf/cm2 and compressive strength of 3.19 MPa. The results showed that the physical (porosity, absorption, and thickness expansion) and mechanical (MOR and compressive strength) tests met the standards of SNI 03-2105-2006, while the MOE test did not meet the standards. For density testing, it complies with SNI 01-4449-2006 standards. The composite board can be used as a substitute for wood for furniture materials.